Examination of the neck veins - Taweevat Assavapokee (2020)
Copyright © 2020 Massachusetts Medical Society. Examination of the neck veins can be easily performed in less than a minute and poses little risk to the patient. Direct examination of the neck veins, estimation of venous pressure, and performance of the abdominojugular reflux test are essential for evaluating right atrial pressure and estimating intravascular volume in patients with dyspnea, edema, or hypovolemia.